Imaji Orang Besikama dalam Tradisi Hamis Batar - Kaho, Eventus Ombri (Jurnal Magistra, 2025)
This study aims to examine how the image of the Besikama people is formed and interpreted through the Hamis Batar tradition, a sacred sacrificial ritual. Using ethnographic methods, this study delves into the cultural practices and spiritual beliefs of the Besikama people, particularly in the context of their interactions with things considered sacred. This analysis utilizes the theoretical scalpel of “the look of the Sacred” introduced by Robert A. Orsi, a concept that goes beyond visual representation to understand a deeper relationship between humans and the divine, or “body beyond the image.” Initial findings indicate that Hamis Batar is not simply a series of ceremonies, but rather a space where the boundaries between the visible (body rituals, offerings) and the invisible (spiritual power, ancestral presence) are blurred. The Besikama people not only look at something sacred, but they also experience and shape it through actions, emotions, and physical sensations. Thus, the image formed is not a static representation, but a dynamic and living reality, continuously constructed and articulated through the practice of Hamis Batar. This research contributes to a richer understanding of how ritual can serve as a vehicle for experiencing and negotiating sacred meaning, going beyond mere symbolism.